Comparative transcriptomic analysis of chicken immune organs affected by Marek’s disease virus infection at latency phases - Ding, Yi; Dunn, John; Zhang, Huanmin; Zhao, Keji; Song, Jiuzhou (Frontiers in Physiology, 2025)
Over the past decades, MDV has dramatically evolved towards more virulent strains and remains a persistent threat to the world’s poultry industry. We performed genome-wide gene expression analysis in the spleen, thymus, and bursa tissues from MD-resistant line and susceptible line to explore the mechanism of MD resistance and susceptibility. We identified genes and pathways associated with the transcriptional response to MDV infection using the robust RNA sequencing approach. The transcriptome analysis revealed a tissue-specific expression pattern among immune organs when confronting MDV. At pathway and network levels, MDV infections influenced cytokine-cytokine receptor interaction and cellular development in resistant and susceptible chicken lines. Meanwhile, we also observed different genetic responses between the two chicken lines: some pathways like herpes simplex infection and influenza A were found in MD resistant line spleen tissues, whereas metabolic-related pathways and DNA replication could only be observed in MD susceptible line chickens. In summary, our research renders new perceptions of the MD progression mechanism and beckons further gene function studies into MD resistance.